2022
DOI: 10.1186/s12905-022-01748-4
|View full text |Cite
|
Sign up to set email alerts
|

Breast self-examination as a route to early detection in a lower-middle-income country: assessing psychosocial determinants among women in Surabaya, Indonesia

Abstract: Background Breast cancer has become a public health concern in Indonesia. Regular breast self-examination (BSE) is considered an important first step for its early detection, especially in countries with limited healthcare access, as it is the case in Indonesia. This study aimed to confirm and assess the psychosocial determinants of intention to perform BSE and BSE performance. Methods The cross-sectional study was conducted on 204 women aged 18–65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Furthermore, we found that lack of awareness about the importance of early detection was the second risk factor for neglecting breast cancer screening. Similar to our findings, a study from Indonesia showed that a lack of awareness about the importance of BSE was a barrier to early detection of breast cancer [ 22 ]. According to previous reports, women are typically hesitant to have cancer screenings unless their doctor recommends it [ 17 , 23 ].…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, we found that lack of awareness about the importance of early detection was the second risk factor for neglecting breast cancer screening. Similar to our findings, a study from Indonesia showed that a lack of awareness about the importance of BSE was a barrier to early detection of breast cancer [ 22 ]. According to previous reports, women are typically hesitant to have cancer screenings unless their doctor recommends it [ 17 , 23 ].…”
Section: Discussionsupporting
confidence: 90%
“…Early detection could identify breast cancer at an early stage reducing poor clinical health. If cancer was diagnosed in an advanced state, it would lead to low survival rates [ 25 , 26 ]. Self-screening encourages women to check abnormal signs of their breasts regularly.…”
Section: Discussionmentioning
confidence: 99%
“…Although policies from WHO, CDC, and developed countries do not support BSE practice as a primary screening tool-several Asian countries, including Indonesia, continue to acknowledge the importance of BSE practice since mammography is not accessible equally among regions [30,31,63,64]. A study by Thaineau et al in Thailand tracked a 1.9 million population regarding the risk of late-stage breast cancer in five years (2012-2017).…”
Section: Discussionmentioning
confidence: 99%